KRITIK SOSIAL GEREJA KEPADA NEGARA MENURUT KACAMATA MICHAEL WALZER - Kolsinus Kalven Benu (Marturia, 2022)
AbstractThe church's social criticism of the State from the development of the early church until the church reformation period, the New Order era, and even the Indonesian reformation order have not run optimally. This is due to the church's closeness to the State to free itself from minority feelings, to be free from suffering and persecution, and to fight for the interests of the church. The such closeness makes it difficult for the church to voice social criticism. This paper intends to rebuild the understanding of the church's social criticism of the State, in light of Michael Walzer's thoughts. According to Walzer, the church needs to have a socially critical attitude towards the government, to convey social criticism. This critical distance helps the church to be free from emotional ties and the influence of certain ideologies with the government to be free to express criticism, especially ahead of general elections and regional head elections. Instead, the church positions itself with marginalized communities and fights for their politics. Abstrak Kritik sosial gereja terhadap Negara sejak perkembangan gereja mula-mula sampai masa reformasi gereja, masa orde baru, bahkan orde reformasi Indonesia belum berjalan secara maksimal. Hal ini disebabkan oleh kedekatan gereja terhadap Negara untuk membebaskan diri dari perasaan minoritas, bebas dari penderitaan dan penganiayaan, serta memperjuangkan kepentingan gereja. Kedekatan yang demikian membuat gereja sulit untuk menyuarakan kritik sosial. Tulisan ini bermaksud membangun kembali pemahaman kritik sosial gereja terhadap Negara, dalam terang pemikiran Michael Walzer. Menurut Walzer, gereja perlu memiliki sikap jarak kritis sosial terhadap pemerintah, agar dapat menyampaikan kritik sosial. Jarak kritik tersebut menolong gereja untuk bebas dari ikatan emosional dan pengaruh ideologi tertentu dengan pemerintah untuk bebas menyampaikan kritik, terlebih menjelang pemilihan umum maupun pemilihan Kepala Daerah. Sebaliknya gereja menempatkan diri bersama masyarakat yang terpinggirkan dan memperjuangkan politik mereka.